2021
DOI: 10.1007/s00170-021-07050-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of milling of low thickness thermoplastic carbon fiber composites in function of tool geometry and cutting conditions

Abstract: The application of Carbon Fiber Reinforced ThermoPlastic matrix composites (CFRTP) is constantly increasing in various industrial sectors. Their mechanical properties and advantages compared to thermoset composite materials make them very important materials. Nevertheless, CFRTP machining generates a current problem due to the anisotropy of these materials, the di culty of impregnation of the reinforcement in the matrix and its low melting temperature. For this reason, the study of conventional operations such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As shown by Fig. in drilling of thermoplastic CF/PEEK [28], CF/pCBT [42] and CF/ABS [30,43], milling of CF/polyurethane [44] and orthogonal cutting of CF/PEEK [45]. Compared to CF/PEKK, the CF/epoxy chips are less intact and contain micro-cracks.…”
Section: Chip Formationmentioning
confidence: 99%
“…As shown by Fig. in drilling of thermoplastic CF/PEEK [28], CF/pCBT [42] and CF/ABS [30,43], milling of CF/polyurethane [44] and orthogonal cutting of CF/PEEK [45]. Compared to CF/PEKK, the CF/epoxy chips are less intact and contain micro-cracks.…”
Section: Chip Formationmentioning
confidence: 99%
“…Substantial drilling and holemaking operations are involved in the riveting and bolting processes, and the tensile strength and fatigue damage of structural components are signi cantly in uenced by high-quality hole-making [8]. The drilling of CFRTP using conventional cutting tools is susceptible to processing damage such as tearing, burrs, and delamination at hole exits [9]- [11], thereby compromising the reliability of the product. The traditional twist drill exhibits a relatively long transverse cutting edge, and during the drilling process of composites, approximately 60% of the total thrust force is generated by the transverse edge, thereby leading to the occurrence of delamination at hole exits [12].…”
Section: Introductionmentioning
confidence: 99%
“…The main difference between CFRTP and CFRP is the variation in matrix performance, leading to notable differences in research on machining methods [12]. In investigating CF/thermoplastic polyurethane (CF/TPU), Sambruno et al [13] conducted milling experiments employing five different milling tools to evaluate the influences of tool geometry and cutting conditions on surface defects and roughness. The findings revealed that the best surface quality was achieved when using the milling tool with a 10°helix angle and 8 teeth under the milling parameter combination of 0.07 mm/tooth and 3000 rpm.…”
Section: Introductionmentioning
confidence: 99%